2020
DOI: 10.3390/ani10050909
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Is a Suitable Tool in the Control of Aujeszky’s Disease Outbreaks in Pigs Using a Population Dynamics P Systems Model

Abstract: Aujeszky’s disease is one of the main pig viral diseases and results in considerable economic losses in the pork production industry. The disease can be controlled using preventive measures such as improved stock management and vaccination throughout the pig-rearing period. We developed a stochastic model based on Population Dynamics P systems (PDP) models for a standard pig production system to differentiate between the effects of pig farm management regimes and vaccination strategies on the control of Aujesz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The effect on the course of the pandemic due to different levels of the population protected by vaccination was compared in a population with 30,000 infected people at time 0. The vaccine was administered at time 0 and the probability of disease transmission from infected to non-infected people in the population was 0.05 or 0.1, when social measures were applied or not, respectively [ 30 ]. The population had no restrictions on normal activities, such as work, schools, or the use of restaurants and bars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on the course of the pandemic due to different levels of the population protected by vaccination was compared in a population with 30,000 infected people at time 0. The vaccine was administered at time 0 and the probability of disease transmission from infected to non-infected people in the population was 0.05 or 0.1, when social measures were applied or not, respectively [ 30 ]. The population had no restrictions on normal activities, such as work, schools, or the use of restaurants and bars.…”
Section: Resultsmentioning
confidence: 99%
“…Population dynamic P system (PDP) models (inspired by the biology of cell function) provide an alternative to traditional modeling for the study of complex problems [ 28 ]. They allow handling of a very large number of interactions in a more efficient way [ 29 , 30 ] and have not previously been applied in human epidemiology. A stochastic model based on PDP modeling has been developed to study the course of COVID-19 epidemics under several different epidemiological scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…PRV always causes reproductive failure in pregnant sows; encephalitis, lung inflammation and high mortality in newborn piglets; and severe, uncontrollable pruritus and lethal neuropathy in non-natural hosts [ 6 7 8 ]. Vaccination is an available strategy for the prevention of PRV infection [ 9 ]; however, the commercially available vaccine against PRV is a potential health risk for other animals [ 10 ]. Despite the eradication of Pseudorabies from domestic pigs in some developed countries [ 11 ], in China, herds immunized with the Bartha-K61 vaccine were shown to be infected with highly virulent PRV variants since late 2011, resulting in severe socioeconomic consequences [ 12 13 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One may argue that controlled management practices, which may be expensive at the early stages of implementation but pay off over time, would be cost-effective compared to vaccination. Some studies (e.g., [ 74 ]) examine the effects of vaccination versus management protocols in animal disease control. Although vaccines may increase costs, studies have shown that efficacious vaccines optimize disease control.…”
Section: Role Of Livestock Farmers and Regulators In Disease Managmentioning
confidence: 99%